Blood Levels of Co-inhibitory-Receptors: A Biomarker of Disease Prognosis in Multiple Sclerosis - Lavon, Iris; Heli, Coral; Brill, Livnat; Charbit, Hanna; Vaknin-Dembinsky, Adi (Frontiers in Immunology, 2019)
Background The clinical course of multiple sclerosis ranges from benign with little disease progression and minimal disability, to malignant disease requiring intensive medical treatment. There are no reliable circulating biomarkers for predicting disease outcome. Co-inhibitory receptors regulate the termination of effective immune responses to infections while limiting autoimmunity and/or immunopathology. Based on this, we studied the potential of circulating co-inhibitory receptor levels as predictive biomarkers of multiple sclerosis outcome. Methods Co-inhibitory receptor [TIGIT (T cell immunoreceptor with Ig and ITIM domains), TIM-3 (T-cell immunoglobulin and mucin domain–containing 3), LAG-3 (lymphocyte activation gene 3), PD-1 (programmed cell death 1), CTLA-4 (cytotoxic T-lymphocyte–associated protein 4)] expression levels in peripheral blood mononuclear cells (PBMCs) were measured using reverse transcription–PCR in 12 healthy controls and 57 patients with untreated multiple sclerosis. All patients were evaluated for disease outcome and paraclinical measures during the following 9–10 years [progression index, Expanded Disability Status Scale (EDSS) score, number of relapses, number of disease modifying therapies (DMTs), baseline brain magnetic resonance imaging T2 lesion volume, oligoclonal bands (OCBs)]. Results Results of 141 patients, 57 (40%) were eligible for analysis. Patients had significantly lower TIGIT levels than the controls (n = 12) (P < .0003). TIM-3 levels were significantly lower in malignant multiple sclerosis versus benign and all non-malignant multiple sclerosis (both, P < .02). LAG-3 levels were significantly higher in benign versus non-benign multiple sclerosis (P < .05). TIM-3 and LAG-3 expression levels correlated significantly with 1-year progression index (r2 = 0.076, P < .05; 0.087, P < .04, respectively) and EDSS score at final visit (r2 = 0.31, P < .04; 0.320.088, P < .04, respectively). Lower LAG-3 levels were associated with higher DMT switching (r2 = 0.67, P < .05.) Interpretation This an initial exploration of the utility of CTLA-4, PD-1, TIM-3, LAG-3, and TIGIT expression levels as prognostic indicators in untreated, recently diagnosed multiple sclerosis. Our results support the value of decreased PBMC expression levels of TIM-3 and LAG-3 at diagnosis as an unfavorable prognostic factor, which is to be confirmed in further studies.